2023
DOI: 10.1177/00323292231168251
|View full text |Cite
|
Sign up to set email alerts
|

Capital Flows and the Eurozone's North-South Divide

Abstract: This article offers a monetary perspective on capital flows and the Eurozone's north-south divide. It argues that finance-centric narratives in comparative political economy rightly emphasize financial instability in the periphery, but that the role of capital flows therein requires clarification. The article draws on post-Keynesian monetary theory, coherent accounting, and balance-of-payments data to make three points. First, the focus on the financial account as a driver of current accounts should be abandon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 41 publications
0
0
0
Order By: Relevance
“…An increase in bank liquidity would not make much difference as they do not need funds from abroad to do so. Kohler (2023) and Febrero et al (2019) demonstrated that the cross-border interbank flows are largely a passive outcome of refinancing decisions of banks. In general, the issue of availability of funds is a cornerstone of the neoclassical loanable funds theory.…”
Section: Soft Budget Constraint Of Banksmentioning
confidence: 99%
“…An increase in bank liquidity would not make much difference as they do not need funds from abroad to do so. Kohler (2023) and Febrero et al (2019) demonstrated that the cross-border interbank flows are largely a passive outcome of refinancing decisions of banks. In general, the issue of availability of funds is a cornerstone of the neoclassical loanable funds theory.…”
Section: Soft Budget Constraint Of Banksmentioning
confidence: 99%